2015
DOI: 10.1002/2014ea000030
|View full text |Cite
|
Sign up to set email alerts
|

Italian seismicity and Vesuvius' eruptions synchronize on a quasi 60 year oscillation

Abstract: The analysis of the time distribution of the major earthquakes that occurred in Italy since 1600 reveals that seismicity alternates periods of higher and lower activities over cycles of about 60 years. The same rhythm is present in the eruptive history of the Vesuvius. The large spatial scale of synchronization leads to suppose an external forcing. A hint on its possible origin comes from climatology, where a quasi 60 year cycle is found for various parameters and processes. A hypothesis, also supported by oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…After 1600, the magnitude of completeness ranges between 5.91 and 6.14. I performed the analysis for the intermediated threshold M w C 6 [the same value used in (Bragato 2015)] and then confirmed the results for M w C 5.8 and M w C 6.2.…”
Section: Data Selectionmentioning
confidence: 61%
See 3 more Smart Citations
“…After 1600, the magnitude of completeness ranges between 5.91 and 6.14. I performed the analysis for the intermediated threshold M w C 6 [the same value used in (Bragato 2015)] and then confirmed the results for M w C 5.8 and M w C 6.2.…”
Section: Data Selectionmentioning
confidence: 61%
“…The occurrence of such events represents a sudden acceleration of seismic activity over the last 30 years: in fact, after two strong earthquakes on 1976 (Friuli earthquake, M w 6.5) and 1980 (Irpinia earthquake, M w 6.8), a magnitude near to 6 was reached just one time, for the Umbria-Marche sequence of September 1997. In a previous study (Bragato 2015), I found that similar accelerations occur cyclically in the seismic history of Italy, more clearly since the seventeenth century. The strong social and economical impact of the earthquakes of 2016 in Central Italy led me to update that analysis and assess the strength of the periodicity.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…The robustness and stability of the result are also checked in various ways: considering the uncertainty associated with the magnitude of each earthquake (i.e., introducing random changes to magnitude); using increasing values of the minimum magnitude; and partitioning the national territory in sub-areas with different seismic characteristics. The second study (Bragato 2015) starts from the same seismic catalog of the present work, furnishes an estimate the overall time density of events since 1100, and concentrates on its oscillatory component since 1600, characterized by a period of about 55 years. The present work neglects the oscillatory component and focalizes on the long-term behavior, with special attention on the pre-1600 trend, with the aim to emphasize and confirm the strong acceleration of the 18th century.…”
Section: Introductionmentioning
confidence: 99%